Adverse reactions to etiological treatment in patients with Chagas disease in the Western Potiguar mesoregion of Brazil: a cross-sectional study - Melo, Henrique Rangelly Gabriel de; Dantas, Aurélio Julio Silva; Jácome, Maria Gabriela Augusto de Medeiros; Lima, Milena Sonely Mendonça Bezerra; Dantas, Antônia Suellen Fernandes; Silva Júnior, José Antonio da; Nascimento, Ellany Gurgel Cosme do; Andrade, Cléber de Mesquita (São Paulo Medical Journal, 2026)
BACKGROUND: Chagas disease is a significant public health challenge in Brazil that is characterized by substantial morbidity and mortality rates, coupled with limited etiological treatment options. OBJECTIVE: To describe and assess the occurrence of adverse reactions resulting from benznidazole treatment in patients from the Western Potiguar mesoregion of Brazil. DESIGN AND SETTING: This retrospective, longitudinal, descriptive observational study included 106 individuals with Chagas disease who attended the Chagas Disease Outpatient Clinic of the Universidade do Estado do Rio Grande do Norte. RESULTS: Among patients subjected to etiological treatment with benznidazole, 40.5% (43/106) experienced adverse reactions, manifesting in 13 distinct forms. The most prevalent reactions occurred primarily in the dermatological and hematological systems. Thus, despite the notable frequency of adverse reactions, their severity remained low, as evidenced by the minimal treatment suspension rate. The treatment demonstrated potential benefits to those affected by the disease. CONCLUSIONS: This study characterized the most frequent adverse reactions to benznidazole, mainly dermatological and hematological reactions, which were mostly mild and rarely led to treatment suspension. Recognizing these events is essential for guiding professionals, enhancing patient confidence, and improving adherence to etiological treatments for Chagas disease.